Increased Carbon Partitioning to Secondary Metabolites Under Phosphorus Deficiency in Glycyrrhiza uralensis Fisch. Is Modulated by Plant Growth Stage and Arbuscular Mycorrhizal Symbiosis - Xie, Wei; Hodge, Angela; Hao, Zhipeng; Fu, Wei; Guo, Lanping; Zhang, Xin; Chen, Baodong (Frontiers in Plant Science, 2022)
Phosphorus (P) is one of the main limiting nutrients for plant growth. Plants regulate carbon (C) allocation belowground and partitioning among root components, such as secondary metabolites (SMs) and non-structural carbohydrates (NSCs), to cope with P deficiency, which could be affected by plant growth stage and arbuscular mycorrhizal (AM) symbiosis. However, the potential interactions between plant growth stage and AM symbiosis remain largely unknown. In a greenhouse pot experiment using licorice (Glycyrrhiza uralensis) as the host plant, we studied C allocation belowground and partitioning in roots in P limited plants in comparison with P-sufficient plants under non-AM and AM symbiosis conditions at two plant growth stages (i.e., early growth stage and late growth stage). Increased C allocation belowground by P limitation was observed only in non-AM plants at the early growth stage. Though root C partitioning to SMs in non-AM plants was increased by P limitation as expected, trade-off patterns were different between two growth stages, with C partitioning to SMs at the expense of NSCs at the early growth stage but at the expense of root growth at the late growth stage. These changes, however, were largely disappeared by well-established AM symbiosis, where more root C was partitioned to root growth and AM fungus without any changes in C allocation belowground and partitioning to SMs under P limitation. These results highlighted that besides improved plant P acquisition ability, AM symbiosis may alter plant C allocation belowground and partitioning between NSCs and SMs to improve plant tolerance under nutrient stress.